Curriculum Design of Child Developmental Psychology Education as a Basis for Mitigating Online Gaming Addiction - Galuh Fairuzela Salsabillah; Nabil Nugraha Hendra; Rifaldy Ahmad Deson (Peradaban Journal of Interdisciplinary Educational Research, 2025)
Online gaming addiction among children today extends beyond psychological concerns into social, academic, and moral dimensions of development. From the perspective of developmental psychology, childhood is a decisive phase for establishing emotional regulation, cognition, and social competence. However, the massive penetration of digital technology often disrupts this trajectory, leading children into addictive behaviors that undermine developmental balance. This article aims to design a curriculum in child developmental psychology education as a basis for mitigating online gaming addiction. Employing a literature study, the research reviews scholarship on digital addiction, child development theories, and curriculum-based intervention strategies. The findings indicate that a curriculum integrated with developmental psychology principles can serve both preventive and rehabilitative functions, focusing on emotional regulation, value internalization, digital literacy, and social skills. The discussion highlights that this curriculum is not merely a pedagogical framework but also a psychosocial intervention responsive to the dynamics of child growth in the digital era. The study recommends collaboration among educators, parents, and psychologists to ensure comprehensive and sustainable implementation. The novelty lies in constructing a developmental psychology–based curriculum explicitly designed as a preventive mitigation mechanism rather than solely as post-addiction intervention, thereby contributing a paradigmatic approach to children’s education in the digital age. Kecanduan gim daring pada anak saat ini tidak hanya menjadi persoalan psikologis, tetapi juga merambah ke dimensi sosial, akademik, dan moral dalam perkembangan mereka. Dari perspektif psikologi perkembangan, masa kanak-kanak merupakan fase krusial untuk membentuk regulasi emosi, kognisi, dan kompetensi sosial. Namun, penetrasi teknologi digital yang masif sering kali mengganggu jalannya perkembangan ini, sehingga anak terjerat dalam perilaku adiktif yang mengganggu keseimbangan tumbuh kembang. Artikel ini bertujuan merancang kurikulum pendidikan psikologi perkembangan anak sebagai basis mitigasi kecanduan gim daring. Dengan menggunakan metode studi pustaka, penelitian ini menelaah kajian terkait adiksi digital, teori perkembangan anak, serta strategi intervensi berbasis kurikulum. Hasil penelitian menunjukkan bahwa kurikulum yang diintegrasikan dengan prinsip-prinsip psikologi perkembangan dapat berfungsi ganda, yaitu preventif sekaligus rehabilitatif, dengan penekanan pada penguatan regulasi emosi, internalisasi nilai, literasi digital, dan keterampilan sosial. Pembahasan menegaskan bahwa kurikulum ini bukan sekadar kerangka pedagogis, tetapi juga strategi intervensi psikososial yang responsif terhadap dinamika perkembangan anak di era digital. Studi ini merekomendasikan kolaborasi antara pendidik, orang tua, dan psikolog untuk memastikan implementasi yang komprehensif dan berkelanjutan. Kebaruan penelitian terletak pada konstruksi kurikulum berbasis psikologi perkembangan yang dirancang secara eksplisit sebagai mekanisme mitigasi preventif, bukan semata intervensi pasca-adiksi, sehingga memberikan kontribusi paradigmatik bagi pendidikan anak di era digital.